Radiofrequency resistant pulmonary atresia with intact septum: the use of Conquest Pro 12 coronary guidewire - İbrahim Cansaran Tanıdır; Erkut Ozturk; Alper Guzeltas; Ender Odemis (KARE Publishing, 2014)
Pulmonary valve atresia with intact ventricular septum, which is a rare congenital heart defect, can be treated either surgically or via transcatheter. Nowadays, in many centers, transcatheter treatment options have become the standard of care for pulmonary atresia, with an intact ventricular septum, for eligible patients. More commonly, radiofrequency wires are used for the perforation of the atretic valve, and subsequently, balloon dilatation is performed. There are limited options for radiofrequency resistant atretic valves. Here, we present the case of 5 day-old male with a radiofrequency resistant atretic pulmonary valve, where perforation was successfully achieved using a Conquest Pro 12 coronary guidewire.